The Effect Of Perceived Ease of Use, Investment Knowledge, And Perceived Risk On Intentions to Purchase of Share in Generation Y - Setyanta, Budi; Kadi, Dian Citaningtyas Ari (AMAR (Andalas Management Review), 2020)
Generation Y investor growth is an attractive phenomenon for research. This study aims to examine the effect of perceived ease of use, investment knowledge, and perceived risk on the intention to buy shares in generation Y in Yogyakarta. The research data collection used convenience sampling technique through online questionnaires. Hypothesis test using multiple linear regression. The results of this study indicate that the research model fulfills the goodness of fit requirements. Remote sensing technology and transaction regulations that are simple and easy to understand as well as adequate investment knowledge affect the intention to buy shares in Generation Y. Complete and accurate information and relatively small investment capital results in not significant potential losses faced by Generation Y.